IMPLEMENTING STORYTELLING METHOD IN EFL CLASSROOM CONTEXT; CHALLENGES AND OPPORTUNITIES - BERTOLI, STEFANUS MARIO; JANGGO, WENDELINUS OSCAR; KARTINI, MARIA; KRISTIANSI , MARIA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This research discusses the use of storytelling method to improve speaking skills in an English as a Foreign Language (EFL) class. The challenges faced by students, English teacher, and researcher in the learning process included students' anxiety, lack of motivation, and different proficiency levels. Using Classroom Action Research, this study involved pre-test and post-test to measure speaking ability and qualitative data from observation and interview. The results show that the storytelling method can be effective in engaging students, building confidence, and improving speaking skills through a dynamic and interactive learning environment. The study noted challenges and opportunities in teaching English speaking skills through the storytelling method. The researcher faced difficulties due to the complexity of language learning, cultural influences and diverse needs of the students. The storytelling method implemented in two cycles showed significant improvement in students' speaking skills, with 63.79% meeting the success criteria in the second cycle. The method not only improved speaking ability, but also encouraged students' critical thinking, creativity and confidence. The teacher also benefited from increased student participation and their ability to create a supportive learning environment. ABSTRAKPenelitian ini membahas tentang penggunaan metode storytelling untuk meningkatkan kemampuan berbicara di kelas Bahasa Inggris sebagai Bahasa Asing (EFL). Tantangan yang dihadapi oleh siswa, guru bahasa Inggris, dan peneliti dalam proses pembelajaran termasuk kecemasan siswa, kurangnya motivasi, dan tingkat kemahiran yang berbeda. Dengan menggunakan Penelitian Tindakan Kelas, penelitian ini melibatkan pre-test dan post-test untuk mengukur kemampuan berbicara dan data kualitatif dari observasi dan wawancara. Hasil penelitian menunjukkan bahwa metode bercerita dapat menjadi efektif dalam melibatkan siswa, membangun kepercayaan diri, dan meningkatkan kemampuan berbicara melalui lingkungan belajar yang dinamis dan interaktif. Penelitian ini mencatat tantangan dan peluang dalam mengajarkan keterampilan berbicara bahasa Inggris melalui metode mendongeng. Peneliti menghadapi kesulitan karena kompleksitas pembelajaran bahasa, pengaruh budaya, dan kebutuhan siswa yang beragam. Metode storytelling yang diterapkan dalam dua siklus menunjukkan peningkatan yang signifikan dalam kemampuan berbicara siswa, dengan 63,79% memenuhi kriteria keberhasilan pada siklus kedua. Metode ini tidak hanya meningkatkan kemampuan berbicara, tetapi juga mendorong pemikiran kritis, kreativitas, dan kepercayaan diri siswa. Guru juga mendapat manfaat dari peningkatan partisipasi siswa dan kemampuan mereka untuk menciptakan lingkungan belajar yang mendukung.